Microwave Heating of Cordierite Ceramic Substrate for After Treatment Systems - Marin, R. C.; Savu, S. V. (Annals of "Dunărea de Jos" University of Galaţi. Fascicle XII, Welding Equipment and Technology, 2020)
Selective catalyst reduction is one of the most affordable and successful technologies aimed at reducing NOx emissions from diesel engines. However, the reduction process can be achieved if a certain temperature is reached for the ceramic substrate of the catalytic core. The required temperatures for catalytic reaction vary from 2500 C to 4500 C depending on the technology applied in the catalytic processes. This paper aims at presenting preliminary research in microwave cordierite heating, which is a type of magnesium aluminium silicate used as ceramic honeycomb substrate (catalyst monolith) in the after treatment system in the automotive industry. The research focused on testing the Mg2Al4Si5O18 composite material (cordierite) for different microwave heating regimes in order to establish the level of microwave power required for fast heating. This application will be subject for the further development of new MW-SCR after treatment systems in order to reduce the NOx emissions at cold start engine or low operating regimes of non-road mobile machinery engines. The ceramic composite material was heated for 5 levels of microwave power, from 600 W to 1400 W, using a 6 kW microwave generator coupled with a matching load impedance tuner, and the temperatures were recorded using an IR pyrometer.